Current Ratio, Return on Asset, and Debt-to-Equity-Ratio on Stock-Price of Sector Property and Real Estate - Tangngisalu, Jannati (Golden Ratio of Finance Management, 2022)
The purposes of this study are: to analyze the current ratio (CR), return on assets (ROA), and debt to equity ratio (DER) both partially and simultaneously affect the stock price of companies listed on the Indonesia Stock Exchange (IDX) in the property sector and real estate. This study uses 31 companies to sample the 55 property and real estate sector from 2017-2021. The sampling technique was carried out using the purposive sampling method. The test used in this study was multiple regression analysis with t-test and f-test. The results show that the current ratio (CR) has a negative and insignificant effect on stock prices in property and real estate sector. In contrast, the debt-to-equity ratio (DER) has a positive but insignificant effect on stock prices in property and real estate sectors. At the same time, Return on Assets (ROA) positively affects stock prices in property and real estate companies. The management of the company is expected to observe the behavior of investors in the capital market, namely by understanding the motives of investors so that the administration can develop a company strategy to attract investors to understand their capital in the company.